Study on the influence of temperature effect on the stress changing law of human lower limbs during Siji sand therapy - Fu, Rongchang; Ahmati, Kuvahan (SPIE, 2022)
Objective: Through experiments and simulation calculations, this paper aims to study the influence of temperature effect on the stress distribution of human lower limbs during sand therapy, so as to provide a theoretical basis for revealing the treatment mechanism of sand therapy. Methods: A sand burial experiment was carried out in the indoor four-season sand therapy system established in the Biomechanics and Heat Transfer Laboratory of the School of Mechanical Engineering of Xinjiang University by simulating the sand therapy field of Xinjiang Turpan Uygur Hospital. The subjects were divided into two groups, each with 16 people. The initial sand burial temperature was controlled at 45℃ and 50℃ respectively, the sand burial thickness was controlled to be 10 cm. Continuous sand therapy was given for ten days, once a day and each lasting 30 minutes. Dynamic changes in pressure and temperature of the lower limb skin surface (in upper, lower, left, right test points) were continuously recorded under the two temperatures and statistically analyzed. The three-dimensional model of the human lower limbs was reconstructed and subject to finite element simulation calculations. Results: ① When the sand burial thickness is 10cm and the initial sand burial temperature is 50℃, the average surface stress of the four test points (upper, lower, left and right) on the human lower limb skin surface increased by 0.093Kpa, 0.173Kpa, 0.167Kpa, 0.169Kpa, respectively compared with those under initial temperature of 45℃. The relationship between temperature and stress is approximately hyperbolic. That is, the stress gradually increases with the decrease of temperature; ②The simulation calculation shows that the maximum equivalent stress of the lower limbs is distributed at the point where muscles contact bones. This is in line with the characteristics of statically indeterminate structure. Compared with 45℃, under the initial sand burial temperature 50℃, the maximum Von mises equivalent stress increased by 0.009Mpa, 0.017Mpa, 0.02Mpa, respectively when sand burial time was t=5min, t=15min, and t=30min. The maximum Von mises equivalent stress increased by 0.046Mpa during the 30min sand burial process. Conclusion: Experiments and simulation studies show that sand therapy temperature produces a certain effect on the lower limb stress of the human body. The temperature stress increases with the prolongation of sand burial time. The lower limb stress state of the human body changes dynamically, which facilitates the massage effect and the blood circulation of removing blood stasis. The higher the initial temperature is, the greater the temperature stress and the better the curative effect is. This carries certain guiding significance for understanding the thermal physical mechanism of sand therapy, guaranteeing the safety and comfort of patients during sand therapy and popularizing sand therapy.